Nafkah Iddah dalam Perspektif Al-Qur’an: Analisis Putusan Pengadilan Agama Jombang Nomor 0015/Pdt.G/2018/PA.Jbg - Andy Saputro, Eko (SAMAWAT: JOURNAL OF HADITH AND QURANIC STUDIES, 2025)
This study explores the implementation of nafkah iddah (maintenance during the waiting period) and mut’ah (consolation gift) for divorced wives, based on the case decision of the Religious Court of Jombang, Case Number 0015/Pdt.G/2018/PA.Jbg. The research stems from the absence of a clear legal standard in Indonesian positive law regarding the amount of nafkah iddah and mut’ah, despite both being recognized as obligations of the husband after divorce. The objective is to analyze the legal basis, judicial considerations, and practical realization of nafkah iddah and mut’ah in divorce cases. This study uses a normative juridical approach combined with a case study and direct interviews with judges. The findings reveal that the amount determined by the judge is influenced by the duration of the marriage, the husband's financial capability, and the agreement between both parties. In this particular case, the court decided on nafkah iddah of IDR 3,000,000, mut’ah of IDR 3,000,000, and nafkah madhiyah of IDR 1,200,000. The decision reflects the principles of justice, propriety, and feasibility, aiming to balance the rights of the wife with the husband's economic ability. The study emphasizes the pivotal role of judges in interpreting and applying Islamic legal values within the framework of Indonesian law.